PERSEPSI MAHASISWA TERHADAP MEDIA PEMBELAJARAN MINI CULTIVATOR PADA MATERI ELEMEN MESIN - Setiawan, Firman; Wiyogo, Wiyogo; Sukardi, Sukardi (Program Studi Pendidikan Teknik Mesin, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Palangka Raya, 2024)
Starting from the limitations of real learning media in learning, this study aims to explore students' perceptions of the use of Mini Cultivator as a learning medium. The research method used is quantitative using the urgency, seriousness, and growth (USG) matrix. The data collection technique uses a questionnaire. The results of the study showed that students' perceptions on the aspect of media effectiveness received the highest priority with a percentage of 25.07%, followed by motivation at 25.06%, usefulness at 25.04%, and innovation at 24.81%. Students' positive perceptions of Mini Cultivator media are reflected in the results of the USG analysis. The results of the assessment on the